2018
DOI: 10.1002/humu.23545
|View full text |Cite
|
Sign up to set email alerts
|

Mutations and common variants in the human arginase 1 (ARG1) gene: Impact on patients, diagnostics, and protein structure considerations

Abstract: The urea cycle disorder argininemia is caused by a defective arginase 1 (ARG1) enzyme resulting from mutations in the ARG1 gene. Patients generally develop hyperargininemia, spastic paraparesis, progressive neurological and intellectual impairment, and persistent growth retardation. Interestingly, in contrast to other urea cycle disorders, hyperammonemia is rare. We report here 66 mutations (12 of which are novel), including 30 missense mutations, seven nonsense, 10 splicing, 15 deletions, two duplications, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 79 publications
(131 reference statements)
3
50
0
1
Order By: Relevance
“…Over the five years prior to sample collection, the plasma arginine levels obtained from quantitative plasma amino acids for these subjects was typically above the upper limit of the normal range despite protein-restriction and nitrogen-scavenging medications (Figure 2). Similar findings have been described in other cohorts of individuals with arginase deficiency 14, 15 . Arginine is a precursor for numerous metabolites including guanidino compounds, and indeed, multiple guanidino compounds including N-acetylarginine, guanidinoacetate, guanidinobutanoate, homoarginine, 4-guanidinobutanal, argininate, and 2-oxoarginine were elevated.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Over the five years prior to sample collection, the plasma arginine levels obtained from quantitative plasma amino acids for these subjects was typically above the upper limit of the normal range despite protein-restriction and nitrogen-scavenging medications (Figure 2). Similar findings have been described in other cohorts of individuals with arginase deficiency 14, 15 . Arginine is a precursor for numerous metabolites including guanidino compounds, and indeed, multiple guanidino compounds including N-acetylarginine, guanidinoacetate, guanidinobutanoate, homoarginine, 4-guanidinobutanal, argininate, and 2-oxoarginine were elevated.…”
Section: Resultssupporting
confidence: 90%
“…Several of these other guanidino compounds have been implicated in the pathogenic mechanism of spastic diplegia, seizures, and intellectual disability in arginase deficiency by mediating increased oxidative stress 30 , disrupting Na+, K+-ATPase activity 31 , and other potential mechanisms of neurotoxicity 32, 33 . The elevations of these potentially neurotoxic compounds derived from arginine are especially concerning given the challenges in normalizing plasma arginine in our subjects and in published cohorts 14, 34 . These guanidino compounds may prove to be useful biomarkers for monitoring efficacy of existing therapies including liver transplantation 35 and may be useful biomarkers for future interventional studies, such as enzyme therapy for arginase deficiency 14 .…”
Section: Discussionmentioning
confidence: 99%
“…An even more severe effect was observed for the mutation p. Gly235Arg. 15 In our patient, in accordance with the literature, homozygous deletion has been detected affecting the p. Gly235Arg region. 16 In 1979, Synderman et al reported an argininemia case diagnosed in the neonatal period due to the diagnosis of metabolic disease in one of siblings.…”
Section: Discussionsupporting
confidence: 91%
“…Although increased plasma arginine is the disease hallmark, arginine may not always be exceedingly high . The diagnosis can be confirmed by enzymatic assays (in erythrocytes) or by genetic analysis . The observation of increased urine orotic acid levels also supports the diagnosis.…”
Section: Recommendations For Specific Disordersmentioning
confidence: 89%